2004
DOI: 10.1016/j.femsre.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of virulence determinants inStaphylococcus aureus: complexity and applications

Abstract: The virulence of Staphylococcus aureus is essentially determined by cell wall associated proteins and secreted toxins that are regulated and expressed according to growth phases and/or growth conditions. Gene expression is regulated by specific and sensitive mechanisms, most of which act at the transcriptional level. Regulatory factors constitute numerous complex networks, driving specific interactions with target gene promoters. These factors are largely regulated by two-component regulatory systems, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
349
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(370 citation statements)
references
References 115 publications
12
349
1
3
Order By: Relevance
“…The expression of virulence genes in S. aureus is controlled by very complicated regulatory circuitry (Bronner et al, 2004;Cheung et al, 2004;Novick, 2003) in which various regulators form a complex network to coordinately regulate different virulence genes. With regard to capsule, we have previously shown that both agr and mgr positively regulate capsule production mostly at the transcriptional level, whereas sarA does not play a role in transcriptional regulation but may have a minor effect at the post-translational level (Luong et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of virulence genes in S. aureus is controlled by very complicated regulatory circuitry (Bronner et al, 2004;Cheung et al, 2004;Novick, 2003) in which various regulators form a complex network to coordinately regulate different virulence genes. With regard to capsule, we have previously shown that both agr and mgr positively regulate capsule production mostly at the transcriptional level, whereas sarA does not play a role in transcriptional regulation but may have a minor effect at the post-translational level (Luong et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…These regulators appear to form a complex network of regulation to coordinately control the virulence gene expression (for reviews see Bronner et al, 2004;Cheung et al, 2004;Novick, 2003). Previously, we showed that agr had a significant effect on capsule production .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of this pathogen to cause such infections relies on its many virulence factors and their coordinated regulation (David & Daum, 2010;Lowy, 1998;Cheung et al, 2004;Bronner et al, 2004;Somerville & Proctor, 2009;Novick & Geisinger, 2008). One of the major virulence factors is the capsular polysaccharide (CP) (O'Riordan & Lee, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The highly adaptable nature of S. aureus, including the rapid development of antibiotic resistance and large tissue tropism, has resulted in it being one of the leading causes of infection in the United States (2). This versatility is made possible by the large array of virulence factors encoded in the S. aureus genome and on mobile genetic elements that are regulated by a complex, interactive network of regulatory systems including two-component signal transduction systems (TCSs) (3)(4)(5).…”
mentioning
confidence: 99%